Development of Bioinformatics Based E-Magazine for Medical Biotechnology Learning: a Case Study of In Silico Research Project - Ihwanul Muslimin, Muhammad Abdul Irhas; Filayani, Muhammad Iqbal (Bioeduca : Journal of Biology Education, 2025)
The rapid development of technology has led to digitalization in various fields, including education. In higher education, students are required to master technology according to their field of expertise. One of the technological applications for biology students is bioinformatics, which can be integrated into medical biotechnology learning through relevant media. This study aims to develop a bioinformatics-based e-magazine as a supporting medium for medical biotechnology learning. The research employed a Research and Development (R&D) method using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The needs analysis involved 66 students, with all participants (100%) agreeing on the importance of developing a bioinformatics e-magazine. The e-magazine design was developed by incorporating the in silico research results of Moringa oleifera leaf compounds as potential agents against lung cancer. Expert validation showed feasibility scores of 91.25% (material) and 85.7% (media), both categorized as very valid. The practicality assessment by users obtained an average score of 89.8% (very practical). Meanwhile, the effectiveness test yielded an average N-Gain score of 0.9 (medium improvement) with an N-Gain percentage of 59.71% (fairly effective). Therefore, the bioinformatics e-magazine can be categorized as feasible, practical, and effective to support medical biotechnology learning.